Al-Tasamuh al-Diniy 'inda Yusuf al-Qardhawiy - Zulkifli Reza Fahmi (Departement of Comparative Study of Religions, 2021)
This paper aims to examine the concept of religious tolerance from Yusuf al-‎Qardhawi's perspective. The descriptive-analytical method is used to describe and analyze the thoughts of Yusuf al-Qardhawi and his relationship with the thoughts of other Muslim scholars. From this research it was found; first, religious tolerance according to Yusuf al-Qardhawi is to give non-Muslims the freedom to choose their religion and not to force them in any form. Second,